Epidemiological Survey on Cervico-Vaginal Prolapse and its Associated Risk Factors in Buffaloes along with an Assessment of Farmers Knowledge - Manasa, Manda; Jyothi, Kancharla; Sai Gunaranjan, Kalubandi; Vidya Sagar, Pentyala (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted to assess the prevalence, risk factors and farmers levels of understanding on cervico-vaginal prolapse (CVP) in buffaloes. The survey was conducted in 910 buffaloes involving 356 farmers of Proddatur region in YSR Kadapa district, Andhra Pradesh, India. The study revealed 10.44% (95/910) genital prolapse, which included CVP 6.92% (63/910) and uterine prolapse 3.52% (32/910). CVP was more prevalent in extensive system of rearing (16.66%), those fed with dry roughage and concentrates (17.07%), those animals that were kept on uneven flooring (12.82%). In the present study, buffaloes in their 7th parity (50.00%) and 9th month of gestation (31.74%) had more number of cervico-vaginal prolapse. Higher numbers of cases were recorded in winter than summer (57.14 vs 42.86%). Amongst 63 CVP affected buffaloes 42.86% experienced dystocia at the time of parturition, while 28.5% experienced occurrence of total uterine prolapse. Birth of male calves was predominant in the cases of CVP (58.73% vs 41.27%) as compared to femal calves. 30.2% of affected buffaloes each experienced RFM and metritis. A questionnarie was prepared to assess the knowledge of farmers on the etiological factors and prevention measures of the CVP and their responses were recorded. It could be concluded that training programs and Kisan melas must be held to enlighten the farmers about the cervico-vaginal prolapse and various reproductive disorders in buffaloes and their preventive measures in the area studied.